FIXING A BASAL BERRIASIAN AND JURASSIC-CRETACEOUS (J-K) BOUNDARY - IS THERE PERHAPS SOME LIGHT AT THE END OF THE TUNNEL? (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Our tentative proposal is that several biological markers have potential to help define any putative boundary in the traditional basal Berriasian interval. That is, between the base of the Berriasella jacobi Subzone and the base of the Pseudosubplanites grandis Subzone, and therefore straddling the base of magnetozone M18r.  Promising micropalaeontological markers are the FADs of Nannoconus steinmannii minor and N. kamptneri minor, plus the base of the Calpionella alpina Zone, and the bloom(s) of Calpionella alpina and Crassicollaria parvula.  The testing and calibration of this constraining event-matrix in the most complete and fossiliferous sections is our task for the near future.
Keywords: Berriasian; J/K Boundary; GSSP; Correlation; Tethyan; Boreal; Austral; Non-Marine; Ammonites; Calpionellids; Calcareous nannofossils; Palynomorphs; Magnetostratigraphy